Объяснение:
a)y³-y^5=y³(1-y²)=y³(1-y)(1+y)
b)2x-2x³=2x(1-x²)=2x(1-x)(1+y)
c)81x²-x^4=x²(81-x²)=x²(9-x)(9+x)
d)4y³-100y^5=4y³(1-25y²)=4y³(1-5y)(1+5y)
e)16m^5-225m^7=m^5(16-225m²)=m^5(4²-(15m)²)=m^5(4-15m)(4+15m)
f)324n^6-625n^8=n^6(18²-(25n)²)=n^6(18-25n)(18+25n)
Объяснение:
a)y³-y^5=y³(1-y²)=y³(1-y)(1+y)
b)2x-2x³=2x(1-x²)=2x(1-x)(1+y)
c)81x²-x^4=x²(81-x²)=x²(9-x)(9+x)
d)4y³-100y^5=4y³(1-25y²)=4y³(1-5y)(1+5y)
e)16m^5-225m^7=m^5(16-225m²)=m^5(4²-(15m)²)=m^5(4-15m)(4+15m)
f)324n^6-625n^8=n^6(18²-(25n)²)=n^6(18-25n)(18+25n)